Correlation Analysis of CBR and Sand Cone Values at the Sub Base of Simpang Tambue-Lhok Dagang Road at STA 1+050 to STA 6+450 - Jufriadi; Fica. A; M. Yanis; F. Radhi; Era S; N. Usrina; Sofyan (LPPM Universitas Malikussaleh, 2022)
The rapid increase in traffic volume will lead to a lower level of road service, so that the traffic flow on the road becomes less smooth. To overcome this situation, efforts are needed, including repairing the pavement layer, one of which is the subbase layer. To determine the bearing capacity and degree of density of the subbase course, CBR field and Sand Cone tests are carried out. The purpose of this study was to analyze the relationship between the CBR value and the Sand Cone, the data were from the results of field and laboratory tests carried out by the executor, the CBR test results obtained were between 60.27% and 72.87% while the Sand Cone was between 59.88% and 62. .71% but after an average CBR and Sand Cone values become 62.48% and 60.44%. From the results of the Product Moment correlation test, a correlation value of -0.225 was obtained. This shows a negative relationship between CBR and Sand Cone values. Furthermore, from the results of the correlation coefficient significance test, it was obtained that t count = -0.730, this t count value is smaller than t table= 2.228 with degrees of freedom 12 -2 = 10 and an error rate of 5% for the 2-party test, so it can be concluded that Ho is accepted and H1 is rejected. This means that there is no significant correlation between CBR and Sand Cone values.